Examination of Paramolar Tubercles in Turkish Population Using Cone Beam Computed Tomography - KAZAK, MAĞRUR; ÇOLAKOĞLU, GİZEM; KAZAK, MAĞRUR; ELÇİN, MEHMET ALİ; SOMTÜRK, ESRA; GÜNAL, ŞÖLEN (My University, 2017)
Paramolar tubercle (PT) is an additional cusp occuring on buccal surface of both upper and lower permanent molars. PT is also known as parastyle when tubercle is present in upper molars, as protostylid when tubercle is present in lower molars. The aim of this study was to evaluate prevalence of PTs in Turkish population with cone beam computed tomography (CBCT). Presence of PT in molar teeth were evaluated retrospectively using CBCT images of 210 patients (102 male, 108 female) between 18-77 years old. A total of 909 teeth were analyzed. Because of various reasons some teeth were excluded and final analyze was done with 653 teeth. Prevalence of PT was found as 2.76 % (18 out of 653). Highest frequency of PT was detected 5 in #27, 4 in #17, 2 in #48 among all molar teeth respectively. In two cases; 2 PTs were on the same tooth, bilateral PT was found only in one case. PT was undetected on upper first molars. Prevalence of PTs on permanent molars is a rare phenomenon in the studied population. Use of CBCT in such anatomic variations will provide valuable and detailed information during treatment modalities. Since this pilot study represents Turkish subpopulation, comprehensive studies with increased number of cases should be undertaken to clarify the prevalence of paramolars in Turkish population. Advanced imaging techniques like CBCT will be more helpful in understanding and detecting exact morphological and anatomical variations of PTs during treatment modalities.